Pengelolaan Pembelajaran Berbasis Alam di RA STIBA Azkiyaa Sukoharjo - Winoto, Ariek Singgih; , Prof. Bambang Sumardjoko, M,Pd; , Dr. Suwaji, M.Kes (2016)
This study is aimed to describe (1) the planning of nature-based learning (2) the implementation of nature-based learning (3) nature-based learning assessment in RA STIBA Azkiyaa Sukoharjo. This study used a qualitative research with an ethnographic approach. Data collection is done through in-depth interviews, observation, and documentation. Analysis technique data uses multiple stages of data collection, data reduction, data presentation, and data verification. Testing the validity of the data uses triangulation techniques and membercheck source. The results of the study show that (1) the learning plan in RA STIBA Azkiyaa Sukoharjo is divided into several stages, setting the development of learners, setting the learning indicators, establishing the concept of matter, setting the theme of learning, and preparing materials and props. (2) implementation based learning nature in RA STIBA Azkiyaa Sukoharjo is done two ways indoor learning and outdoor learning with the concept of the natural environment as the basis of learning, (3) assessment based learning nature in RA STIBA Azkiyaa Sukoharjo consists of three activities, namely through observation, anecdotal notes and fortofolio. Keywords: early childhood education, management, nature-based learning